2001
DOI: 10.5751/es-00267-050104
|View full text |Cite
|
Sign up to set email alerts
|

Population Genetic Aspects of Pollinator Decline

Abstract: Abstract•

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
102
1
6

Year Published

2002
2002
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(114 citation statements)
references
References 118 publications
(103 reference statements)
5
102
1
6
Order By: Relevance
“…As many hymenopterans exhibit CSD (Cook and Crozier, 1995), they are expected to have even lower effective population sizes than previously predicted due to haplodiploidy alone. Hymenopteran species usually exhibit lower levels of genetic variation, when compared to diploid insects (reviewed by Packer and Owen, 2001) even when the confounding effects of haplodiploidy and social behavior are removed (Hedrick and Parker, 1997;Packer and Owen, 2001), consistent with the present analysis. Surprisingly low empirical estimates of N e (5100) for natural hymenopteran populations (Zayed and Packer, 2001;Antolin et al, 2003;Zayed et al, 2004) also lend support to the view that hymenopterans with CSD have lower N e than previously expected.…”
Section: Discussionsupporting
confidence: 77%
“…As many hymenopterans exhibit CSD (Cook and Crozier, 1995), they are expected to have even lower effective population sizes than previously predicted due to haplodiploidy alone. Hymenopteran species usually exhibit lower levels of genetic variation, when compared to diploid insects (reviewed by Packer and Owen, 2001) even when the confounding effects of haplodiploidy and social behavior are removed (Hedrick and Parker, 1997;Packer and Owen, 2001), consistent with the present analysis. Surprisingly low empirical estimates of N e (5100) for natural hymenopteran populations (Zayed and Packer, 2001;Antolin et al, 2003;Zayed et al, 2004) also lend support to the view that hymenopterans with CSD have lower N e than previously expected.…”
Section: Discussionsupporting
confidence: 77%
“…These estimates suggest that a large part of the difference between the two estimates (48 vs 16.4) of N e reported by Ellis et al (2006) might be ascribed to the effect of worker reproduction. Hymenopteran species usually exhibit lower levels of genetic variation, when compared with diploid species (reviewed by Packer and Owen (2001)). Crozier and Pamilo (1996) predicted that although male production by workers may lead to lower levels of genetic variation by its effect on N e , it is unlikely that the effect is larger.…”
Section: Resultsmentioning
confidence: 99%
“…Inbreeding could also have contributed to the reduction in populations size due to the deleterious effects of homozygosis in loci responsible for sex determination in these bees, leading to the appearance of diploid drones in colonies. Packer and Owen (2001) have already showed that endangered species of some Lepidoptera had significantly lower levels of heterozygosity when compared with nonendangered species of the same order. The effective reduced population size and the occurrence of population 672 Tavares et al bottlenecks have also been cited as possible reasons for the low levels of polymorphism found in the ant Diacamma indicum (Viginier et al, 2004), andGoropasiinaya et al (2001) reported a reduction in the diversity of microsatellites in small and geographically isolated populations of the ant Formica cinerea.…”
Section: Discussionmentioning
confidence: 99%